Effects of female labor participation on smoking behavior in Japan: Selection model approach - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2016)
Using individual level data (the Japanese General Social Survey), this paper aims to explore how interaction between genders contributes to the cessation of smoking in Japan, where females are distinctly less inclined to smoke than males. Controlling for various socioeconomic factors and selection bias, I find through a Heckman-type selection estimation that rates of female employment in workplaces are negatively associated with male smoking but not with female smoking. These results suggest that male smokers are more inclined to cease smoking when they are more likely to have contact with nonsmokers of the opposite sex. Overall, this empirical study provides evidence that the psychological effect of the presence of people in one's surroundings has a direct significant effect upon smoking behavior. However, this effect is observed only among males and not females.
Keywords: I10; Z13; 330; Female labor participation; Labor market; Smoking behavior